2013
DOI: 10.1038/ng.2826
|View full text |Cite
|
Sign up to set email alerts
|

Recessive mutations in a distal PTF1A enhancer cause isolated pancreatic agenesis

Abstract: The contribution of cis-regulatory mutations to human disease remains poorly understood. Whole genome sequencing can identify all non-coding variants, yet discrimination of causal regulatory mutations represents a formidable challenge. We used epigenomic annotation in hESC-derived embryonic pancreatic progenitor cells to guide the interpretation of whole genome sequences from patients with isolated pancreatic agenesis. This uncovered six different recessive mutations in a previously uncharacterized ~400bp sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
274
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(293 citation statements)
references
References 40 publications
13
274
0
6
Order By: Relevance
“…The importance of distal regulatory elements like enhancers in human disease was suggested years ago by the observation in many genome-wide association studies that causal variants are very often identified distant from transcribed genes (Helgadottir et al, 2007). This suggestion has been confirmed in more recent studies showing that the disruption of the function of these regulatory elements can lead to changes in gene expression and disease phenotypes (Weedon et al, 2014;Lupiáñez et al, 2015).…”
Section: Introductionsupporting
confidence: 55%
“…The importance of distal regulatory elements like enhancers in human disease was suggested years ago by the observation in many genome-wide association studies that causal variants are very often identified distant from transcribed genes (Helgadottir et al, 2007). This suggestion has been confirmed in more recent studies showing that the disruption of the function of these regulatory elements can lead to changes in gene expression and disease phenotypes (Weedon et al, 2014;Lupiáñez et al, 2015).…”
Section: Introductionsupporting
confidence: 55%
“…[16][17][18] Variation in transcriptional regulatory elements is also important, and pathogenic regulatory variants have been identified for a number of Mendelian disorders. [49][50][51][52] One specific example is the alteration of SORT1 (MIM: 602458) expression by a transcriptional regulatory variant that can increase the risk of myocardial infarction by 40%. 53 However, the relationship between variation and disease in transcriptional regulatory elements is poorly understood.…”
Section: Annotating Every Possible Variant In Disease-related Functiomentioning
confidence: 99%
“…Such mutations are frequently large deletions or duplications, but may also consist of single‐nucleotide mutations, similar to those most frequently induced by ENU, as found in isolated pancreatic agenesis, and recently described in the promoter region of ovo‐like zinc finger 2 ( OVOL2 ) in families with autosomal‐dominant corneal endothelial dystrophies 71. Mutations upstream of PTF1A were found to reduce the expression of PTF1A , whereas mutations in the OVOL2 promoter were able to induce OVOL2 expression, likely leading to aberrant ectopic OVOL2 expression in the developing cornea 70, 71. Either of these two molecular mechanisms could account for the dominant disease presentation in Hvf mice, eg, through a dosage effect due to a reduction in the level of a critical transcript, or through ectopic induction of a transcript, and either of these may be time and/or spatially specific.…”
Section: Discussionmentioning
confidence: 68%
“…These include triphalangeal thumb/preaxial polydactyly (autosomal dominant with variable penetrance), due to mutations in the ZPA regulatory sequence, a long‐range cis‐acting regulator of Sonic Hedgehog ( SHH ) gene expression67, 68, 69; and autosomal recessive isolated pancreatic agenesis due to noncoding mutations downstream of pancreas‐specific transcription factor 1a ( PTF1A ) 70. Such mutations are frequently large deletions or duplications, but may also consist of single‐nucleotide mutations, similar to those most frequently induced by ENU, as found in isolated pancreatic agenesis, and recently described in the promoter region of ovo‐like zinc finger 2 ( OVOL2 ) in families with autosomal‐dominant corneal endothelial dystrophies 71.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation